Synergistic interaction and activation of the opioid receptor-NO–cGMP–K+ channel pathway on peripheral antinociception induced by the α-Bisabolol-diclofenac combination - Ortiz, Mario I. (Frontiers in Pharmacology, 2023)
Introduction: The local peripheral combination of analgesic drugs with herbal derivatives may have beneficial effects. Information on the action mechanism of these interactions between drugs is scarce. Therefore, the main of the present study was to determine the pharmacological interaction and action mechanism of the combination α-Bisabolol and diclofenac. Methods: Rats were injected in the dorsal surface of the right hind paw with 1% formalin. Rats received subcutaneous injections in the dorsal surface of paw of vehicles or increasing doses of α-Bisabolol, diclofenac or their combination before formalin injection into the paw. Antinociception of the α-Bisabolol + diclofenac combination was evaluated with and without the local treatment of naloxone, metformin, NG-nitro-L-arginine methyl ester (L-NAME), 1H- (1,2,4)-oxadiazolo (4,2-a) quinoxalin-1-one (ODQ), glibenclamide, glipizide, 4-aminopyridine, tetraethylammonium, apamin, or charybdotoxin. Results: α-Bisabolol, diclofenac or α-Bisabolol-diclofenac combinations produced significant antinociception in the rat (p < 0.05). The experimental effective dose (ED) value of 109.2 µg/paw was different significantly of the theoretical effective dose (ED) of 245.7 µg/paw (synergism). Blockers significantly reverted the antinociception produced by the synergistic combination of α-Bisabolol and diclofenac. Discussion: Data showed a synergism of the α-Bisabolol-diclofenac combination and the activation of the opioid receptor-Nitric Oxide–cyclic GMP–K+ channels pathway and a biguanide-dependent mechanism in order to produce the potentiation of its peripheral antinociception in the formalin test.